1987
DOI: 10.5144/0256-4947.1987.202
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Infestation in Expatriates in Riyadh, Saudi Arabia

Abstract: The prevalence of intestinal pathogenic parasitic infestation in expatriates working in Riyadh, Saudi Arabia was assessed. Stool specimens were collected from 2,496 non-Saudis for routine microscopic examination. Pathogenic parasites were found in 55.7% of the total with multiple pathogens in 10.5% of positive cases. The common parasites were Entamoeba histolytica (34.3%), Ascaris lumbricoides (8.5%), and Giardia lamblia (5.1%). To a lesser extent Hymenolepis nana (2.8%), Trichuris trichiura (2.5%), Taenia spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Previous studies in Saudi Arabia revealed high prevalence rates of infection with intestinal parasitic diseases among specific populations including food handlers (14%), Riyadh school children (14.2%), expatriates (55.7%), the Abha community (13.2%) and patients attending hospitals (31.3%) (Abdel Hafez et al . 1987; Ahmed & Bolbol 1989; Al‐Fayez & Khogheer 1989; Al‐Madani et al .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Saudi Arabia revealed high prevalence rates of infection with intestinal parasitic diseases among specific populations including food handlers (14%), Riyadh school children (14.2%), expatriates (55.7%), the Abha community (13.2%) and patients attending hospitals (31.3%) (Abdel Hafez et al . 1987; Ahmed & Bolbol 1989; Al‐Fayez & Khogheer 1989; Al‐Madani et al .…”
Section: Introductionmentioning
confidence: 99%
“…5 As most of these expatriate working as food handlers, baby sitters and domestic helpers hail from parasitic endemic countries, there are possibilities for them to carry them as asymptomatic carriers and to transmit them. [6][7][8] In contrast to protozoan infections, the prevalence of helminthes infections in our study was significantly low (8%) and it was mainly seen in expatriate population. Similar observations have been made in studies performed in the neighboring countries.…”
Section: Discussionmentioning
confidence: 71%
“…All 3 types of cestodes are zoonotic but C. fasciolaris (larval stage of the cat cestode Taenia taeniaeformis) has rare human cases (Deplazes et al 2019). Both H. nana and H. diminuta can infect humans, and in cases of serious infection, they can cause symptoms such as diarrhea and abdominal pain (Abdel-Hafez 1987;Imam et al 2015;Ismail et al 2018;Rabiee et al 2018;Kandi 2019;Shahnazi et al 2019). An increase in temperature and poor sanitation conditions in an environment can increase the probability of transmission of these zoonotic parasites to humans (Paramasvaran et al 2009).…”
Section: Discussionmentioning
confidence: 99%